Epidemiological profile and treatment of cystic echinococcosis hospitalized cases in Morocco between 2011 and 2021 - Ilham Benmoujjane; Souad Bouhout; Aicha mehdioui; Houda Chebli; Meryem Zabarra; Mohammed Akrim; Hassan Chrifi; Touria Benamar (Clinical Epidemiology and Global Health)
Background/objective: Cystic Echinococcosis (CE) is a globally spread zoonotic disease. In Morocco, CE is endemic. The objective was to study Morocco's epidemiological profile and management of hospitalized patients with CE. Methods: This research was done retrospectively over 11 years (2011–2021). It included 7385 cases from all regions of Morocco. Results: Between 2011 and 2021, the annual incidence decreased from 4.55 to 1.18 (per 100,000 population). The patients' ages varied from one to 115 years. The sex ratio of women to men was 1.54. Rural areas accounted for 62.96 % of the patients. The diagnostic method commonly used was the ultrasound (67.62 %). The liver (80.85 %) was the most affected organ, followed by the lungs (15.68 %). Type I cysts accounted for 56.35 % of all HC cases. Surgery was performed in 97.33 % of the patients, with 57.01 % being conservative. The outcome was favorable for 98.48 % of the cases. The Average Length of Stay (ALOS) in the hospital for CE patients was 11 days. Conclusion: Significant progress has been made towards achieving the goal of CE eradication by 2030, but Morocco still faces a significant threat due to the high number of hospitalized cases and resulting deaths.